From writing as a counterspell to a manifesto for performative writing at university (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This publication is the combination of two performative texts from a doctoral research in Performing Arts that embody experiences and reflections of a body that moves between languages, fields and practices, works in collectives, guides, mentors, dances, writes and publishes collectively in the south of Brazil. Starting from a writing that testifies to the experience of the performative practices of Renata Felinto and Grada Kilomba to reveal the noise of the colonial wound in the bodies that live in this Westernized society, including this one who writes, and to move thoughts on the insurgency of discourses and practices in academia, both through their themes and the modes of writing.
Keywords: performative Writing; performance; Renata Felinto; Grada Kilomba; academic writing